Persistent left sided superior vena cava: the perplexity of PICC - Abu Bakar, Intan Bazilah; Phuar, Ai Ping; Ch’ng, Li Shyan; Abdul Ghani, Zulkifli Zaki (IIUM Press, 2020)
Introduction: Persistent left superior vena cava is a rare anatomic anomaly, found only about 0.3-0.5% of the general population. On top of that, about 12% of patient has associated congenital cardiac anomaly. Typically, this anomaly is found as an incidental finding as patient is generally asymptomatic. However, it is important to recognize such anomaly in order to avoid complication during placement of central venous catheter. Case report: We herein report a case of an incidental finding of persistent left sided superior vena cava (SVC) upon insertion of peripherally inserted central catheter (PICC). Initial difficulty and perplexity during insertion of PICC with the tip of catheter keep pointing towards the left side of the heart leads us to proceed with central venogram that confirmed such anomaly.